2016
DOI: 10.1002/hbm.23475
|View full text |Cite
|
Sign up to set email alerts
|

Cortico‐limbic connectivity in MAOA‐L carriers is vulnerable to acute tryptophan depletion

Abstract: MAOA-L carriers were more susceptable to a central 5-HT challenge in cortico-limbic networks. Such vulnerability of the cortical serotonergic system may contribute to the emergence of antisocial behavior after systemic challenges, observed as gene-environment interaction. Hum Brain Mapp 38:1622-1635, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 115 publications
(136 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, methodological differences may also explain why others have reported ATD effects. For example, seed-based approaches provide more power due to strong a priori hypotheses regarding the functional connectivity of the seed region and, therefore, capture more subtle connectivity changes (Eisner et al, 2017). Similarly, other ATD studies use resting-state data but analyze measures, like fractional amplitude Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, methodological differences may also explain why others have reported ATD effects. For example, seed-based approaches provide more power due to strong a priori hypotheses regarding the functional connectivity of the seed region and, therefore, capture more subtle connectivity changes (Eisner et al, 2017). Similarly, other ATD studies use resting-state data but analyze measures, like fractional amplitude Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…1). These various 5-HT-related polymorphisms may form an interactive system that determines the aetiology and prognosis of various forms of affective disorder (17,(99)(100)(101)(102) . However, the most evidenced serotonergic genetic influence on behaviour is the 5-hydroxytryptamine transporter-linked promoter region (5-HTTLPR) polymorphism of the serotonin transporter gene (SLC6A4) (103)(104) .…”
Section: Role Of Genetics In Moderating Effects Of L-tryptophan Supplmentioning
confidence: 99%
“…In addition, heathy L- MAOA carriers showed prominent structural and functional changes in the corticolimbic network, which plays a crucial role in regulating emotional states during the recall of negative events 17 . Recent work showed that L- MAOA carriers are more susceptible to pharmacological regulation by serotonin, with changes in the corticolimbic network, indicating a possible link between the serotoninergic system and MAOA genotype 38 . The effects of MAOA genotype on the dopaminergic system remain controversial.…”
Section: Introductionmentioning
confidence: 99%